(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2024)
This article analysed and compared two novels: Sahlesilasse Birhanemeskel’s Firebrands and W.E Mkufya’s The Wicked Walk following a thematic analytical framework. The article tries to explore the major themes of the two novels. The novels were selected from two different African counters: Firebrands from Ethiopia and The Wicked Walk from Tanzania. The study followed a qualitative research design. A content analysis checklist was followed as the main analytical tool. Common themes portrayed by the two East African novelists have often been misunderstood as the authors lived in two different counties facing colonialism and liberation differently. Tanzania was a British colony and Ethiopia remained a free country. Readers often expect the two authors present a negative presentation of social class in each society. Living into two different worlds, the two authors are expected to depict entirely different images of women in the two Eastern Africa societies. Several thematic analyses have been conducted on African literature by several researchers. Such studies also contributed a lot to the development of literature in the Africa.